The Effect of Customer Orientation on Marketing Performance Through Product Innovation as a Mediating Variable - Alipia, Maya; Danial, R Deni Muhammad; Saori, Sopyan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Marketing performance in culinary MSMEs in Sukabumi City is suspected to be caused by low product innovation and customer orientation. The purpose of this study was to analyze the effect of customer orientation on marketing performance with product innovation as a mediating variable. This study used quantitative method with descriptive causal approach. The study population was culinary MSMEs in Sukabumi City registered at the cooperative office, with a sample of 135 MSMEs randomly selected through probability sampling technique. Data collection was conducted through observation, questionnaires, and literature study, and data analysis using Structural Equation Modeling (SEM) method with the help of AMOS software. The results showed that customer orientation has a significant positive effect on product innovation (C.R. = 5.551, p < 0.05), and customer orientation has a significant positive effect on marketing performance (C.R. = 4.517, p < 0.05). However, product innovation has no significant effect on marketing performance (C.R. = 0.984, p > 0.05). Product innovation partially mediates the relationship between customer orientation and marketing performance (Z value = 3.168 > 1.978). In conclusion, customer orientation is important to improve marketing performance, although product innovation is not the dominant mediating factor.